Pembekuan semen lele dumbo (Clarias gariepinus Burchell 1822) sebagai model kriopreservasi semen ikan [Freezing of african catfish semen (Clarias gariepinus Burchell 1822) as a model of cryopreservation fish semen] - Lutfi Lutfi; R. I. Arifiantini; B. Purwantara (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2011)
Effect of four types of diluents and four concentrations of dimethyl sulfoxide (DMSO) (5%, 10%, 15% and 20%) of African catfish spermatozoa motility were evaluated after storage at freezing temperatures. Efforts African catfish semen cryopreservation in 16-thinning treatment combinations consisting of several stages, namely: preparation of dilution, mixing with DMSO diluents, packing semen in 0.3 mL straw, equilibrasi semen at a temperature of the refrigerator at 4oC for 30 minutes, freezing semen in nitrogen vapor liquid with a height of 6.5 cm for 10 min and subsequent storage of semen in the container of liquid nitrogen (-196oC) for further analyzed post-thawing motility (PTM). Results of analysis PTM, seen the level of sperm motility was shown at PiD15 treatment (45.7 ± 4.3%) and the lowest in P2D20 treatment (14.5 ± 13.2%). The best diluent on this observation is a diluent containing NaCl, KCl, CaCl2 and NaHCO3. The best concentration of DMSO is 15% DMSO concentration. While the best interaction between the diluent with the concentration of DMSO is PiD15 treatments containing NaCl, KCl, CaCl2 and NaHCO3 with a combination of 15% DMSO concentration. Conclusion, making efforts to cryopreservation of African catfish semen can use a diluent containing NaCl, KCl, CaCl2 and NaHCO3 with a combination of 15% DMSO concentration. AbstrakEfek empat jenis pengencer dan empat konsentrasi dimetil sulfoksida (DMSO) (5%, 10%, 15% dan 20%) dari motilitas spermatozoa ikan lele dumbo dievaluasi setelah penyimpanan pada suhu beku. Upaya kriopreservasi semen lele dumbo terhadap 16 kombinasi perlakuan yang terdiri atas beberapa tahap, yaitu: persiapan pengenceran semen lele dumbo; pencampuran dengan bahan pengencer DMSO; pengepakan semen di dalam straw 0,3 ml; equilibrasi pada suhu lemari es pada suhu 4oC selama 30 menit; semen lele dumbo dibekukan di atas uap nitrogen cair dengan tinggi 6,5 cm selama 10 menit dan selanjutnya disimpan dalam wadah nitrogen cair (-196oC) untuk dianalisis lanjut guna melihat postthawing motility (PTM). Hasil analisis PTM, terhadap tingkat motilitas spermatozoa lele dumbo, terlihat bahwa nilai tertinggi pada perlakuan PiD15 (45,7±4,3%) dan terendah pada perlakuan P2D20 (14,5±13,2%). Pengencer terbaik ada-lah pengencer yang mengandung NaCl, KCl, CaCl2, dan NaHCO3. Konsentrasi terbaik DMSO adalah konsentrasi DMSO 15%. Sementara interaksi terbaik antara pengencer dengan konsentrasi DMSO adalah PiD15 perlakuan yang mengandung NaCl, KCl, CaCl2, dan NaHCO3 dengan kombinasi konsentrasi DMSO 15%. Kesimpulan, upaya kriopreservasi sperma lele dumbo dapat menggunakan pengencer yang mengandung NaCl, KCl, CaCl2, dan NaHCO3 dengan kombinasi konsentrasi DMSO 15%.